Diseño, implementación y evaluación de un sistema biofísico demostrativo para el tratamiento de aguas residuales domesticas provenientes de las descargas de alcantarillado del barrio San Miguel de la Hueca del cantón Centinela del Cóndor - Sarango Sarango, Vinicio Salvador (2016)
A demonstrative biophysical treatment system was designed, implemented and evaluated to treat the wastewater of the Hueca neighborhood that belongs to Centinela del Condor canton. For which it was initiated with the identification of the discharge, then with the measurement of flow rates for a week, applying the volumetric method, the Ph and temperature were determined, after the physical, chemical and microbiological characterization of a water residual sample in situ. In the same way, the design of the system was continued using civil engineering formulas using the AUTO CAD program, then proceeded with the construction and operation of the system with the use of the aquatic plant “Water fern” which has a potential in sewage, this specie was monitored for 2 months, 8 days, and by last the final analysis of the treated waste water was carried out. Finally, the initial results are obtained by the laboratory in which the parameters that are outside of the maximum permissible limit are: Total suspended solids, phosphorus, BOD, oils and fats, surfactants, and fecal coliforms. While through the implementation of the treatment system, the results obtained by the laboratory show that the parameters mentioned above have been removed and comply with the maximum permissible limit of the Ministerial Agreement 097. In conclusion, a 20% removal and degradation was obtained in the COD, by the BOD of 23.08% and in the fecal coliforms of 44.83%. This is due to the well-formulated design, which resulted in 94.44% of the sediment being retained in the sedimentation tank while 5.44% was passed to the filtration system.